1999
DOI: 10.1097/00000539-199910000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Low-Flow Anesthesia and Reduced Animal Size Increase Carboxyhemoglobin Levels in Swine During Desflurane and Isoflurane Breakdown in Dried Soda Lime

Abstract: The present study shows that the use of desflurane with desiccated carbon dioxide absorbents in pediatric anesthesia can produce a dangerous carbon dioxide intoxication, especially with low-flow anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The different responses to LFA with regard to COHb in younger vs older children were likely due to patient size, 12 14 since CO exposure results in a greater increase in COHb in smaller subjects. 12 The observation that COHb did not decrease after HFA is probably explained by the lack of offgassing. 3 15 Off-gassing, the displacement of CO from haemoglobin by oxygen might have been minimized by using air as the fresh gas in the breathing circuit.…”
Section: Discussionmentioning
confidence: 99%
“…The different responses to LFA with regard to COHb in younger vs older children were likely due to patient size, 12 14 since CO exposure results in a greater increase in COHb in smaller subjects. 12 The observation that COHb did not decrease after HFA is probably explained by the lack of offgassing. 3 15 Off-gassing, the displacement of CO from haemoglobin by oxygen might have been minimized by using air as the fresh gas in the breathing circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Halothane and sevoflurane did not produce detectable amounts of carbon monoxide, and carboxyhemoglobin levels did not increase above baseline values (93). The effects of animal size, anesthetic concentration, and fresh gas flow rate on inspired carbon monoxide and carboxyhemoglobin production were studied (26). Compared with isoflurane, carbon monoxide and carboxyhemoglobin concentrations were significantly greater with desflurane, particularly in smaller pigs.…”
Section: Carbon Monoxidementioning
confidence: 99%
“…2. This moiety may degrade to carbon monoxide under conditions of high anesthetic, dry carbon dioxide absorbent, increasing temperature, and low gas flow rates (26,74,203,204). Since sevoflurane and halothane lack the difluoro-methyl moiety, no degradation to carbon monoxide can occur.…”
Section: Carbon Monoxidementioning
confidence: 99%
“…Even though the conventional CO 2 absorbent Wakolime™ A contains the strong bases NaOH and KOH, it did not increase the concentrations of CO, which leads to an increase in COHb. Bonome et al 7 reported that fresh gas flow had a diluting effect on CO concentrations in the circuit. Tang et al 12 also reported results of analysis using a regression model that predicted decreases of approximately 7.7 ppm and 5.9 ppm in peak and mean CO concentrations for an increase in gas flow rate by 1.0 l.min -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Smokers have a high incidence of postoperative respiratory complications such as pneumonia 2,3 , and smoking can also increase the concentration of carboxyhemoglobin (COHb) up to 5% to 10% 4 , a concentration that inhibits the preferred binding of haemoglobin (Hb) with oxygen, leading to cardiac events during anaesthesia 5 . On the other hand, carbon monoxide (CO) can be produced from degradation of isoflurane by soda lime 6 , especially with dry soda lime 6,7 , or by the use of a low-flow anaesthetic technique 7,8 . An unfavourable increase in COHb in smoking patients is therefore anticipated under these conditions.…”
mentioning
confidence: 99%